On the structural determinants of growth-at-risk - Martin Gächter; Martin Geiger; Elias Hasler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
We examine structural differences in growth vulnerabilities across countries associated with financial risk indicators. Considering trade openness, financial sector size, the public spending ratio and government effectiveness, our findings suggest the existence of a structural gap and a risk sensitivity gap. Hence, structural country characteristics not only drive level differences in growth-at-risk (GaR) but also give rise to differences in the responsiveness of GaR to financial risks. Furthermore, we show that the impact of structural characteristics varies over the forecasting horizon. A proper understanding of structural country characteristics in the context of the GaR framework is important to facilitate the use of the concept in macroprudential policy.
Keywords: E27; E32; E44; F43; G01; G20; G28; 330; Growth-at-risk; vulnerable growth; structural characteristics; macroprudential policy